Does ground-reaction force influence post-impact ball speed in the tennis forehand groundstroke? - Shimokawa, R.; Nelson, A.; Zois, J. (Sports Biomechanics, 2022)
Motion of the rear leg during a tennis forehand was previously reported to influence the ball speed. However, impact of a kinetic measure such as the ground-reaction force (GRF) on forehand ball speed has not been investigated. The aim of this study was to investigate the influence of GRF on forehand ball speed and identify the most influential component of GRF related to overall higher ball speeds. Nine tennis players (eight males, one female) were invited to participate. Three testing sessions were conducted. Each session consisted of maximal forehand ball-speed testing and seven forehands at three ball speeds; fast (100%), medium (90%) and slow (80%). GRF and post-impact ball speed were measured for each stroke. Of all the individual GRF vectors, peak anterior-posterior force best explained the changes in ball speed, where 26% (R2 = 0.26) of ball speed variance can be explained by this force vector alone. In a stepwise fashion, adding peak lateral force to the model explained a further 7% (R2 = 0.33). Combining peak anterior-posterior, medial-lateral and vertical forces explained a total of 37% (R2 = 0.37). Peak anterior-posterior force appears to be the most influential ground-reaction force affecting forehand post-impact ball speed.